The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13595-018-0747-1
|View full text |Cite
|
Sign up to set email alerts
|

Selection of arbuscular mycorrhizal fungal strains to improve Casuarina equisetifolia L. and Casuarina glauca Sieb. tolerance to salinity

Abstract: & Key message Selection of the best salt-tolerant combination of Casuarina sp. and arbuscular mycorrhizal fungi (AMF) is one of the key criteria for successful setup of saline land rehabilitation program. & Context Land salinization is a serious problem worldwide that mainly leads to soil degradation and reduces crop productivity. These degraded areas could be rehabilitated by planting salt-tolerant species like Casuarina glauca Sieb. and Casuarina equisetifolia L. These are pioneer plants, able to form symbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The higher frequencies and intensities in co-inoculated P.agg + Rf plants would explain the salt tolerance of this strain. The work of Djighaly et al (2018) showed significant metabolic activity of R. fasciculatus at 300 mM NaCl. But also to the additional effect of PGPR which improves the phosphate nutrition of the plant (Egamberdieva et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The higher frequencies and intensities in co-inoculated P.agg + Rf plants would explain the salt tolerance of this strain. The work of Djighaly et al (2018) showed significant metabolic activity of R. fasciculatus at 300 mM NaCl. But also to the additional effect of PGPR which improves the phosphate nutrition of the plant (Egamberdieva et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…This effect was related to an increase in K+ content accompanied by an effective decrease in Na+ in plant tissues. The positive effect co-inoculation P. agg + Rf on growth parameters could be explained by the fact that P. agglomerans, is a halophilic, nitrogen-fixing and phosphate-solubilizing strain, capable of producing of indole acetic acid (AIA) up to 600 mM NaCl (Hasfa, 2014) and AMF (R. fasciculatus) in improving salt tolerance stress among Casuarina species (Djighaly et al, 2018). In the presence of salt, these microorganisms participate in the selective absorption of ions such as phosphorus, nitrogen and magnesium and in the reduction of Na+ ion absorption (Giri and Mukerji, 2004;Chen et al, 2014;Paul and Sinha, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, 15 PCD-related genes were induced by SA or JA to participate in the salt stress response. Interestingly, selection of appropriate fungal strains is crucial for improving C. equisetifolia performance in saline soils ( Djighaly et al, 2018 ). The effect of Frankia symbiosis on salt tolerance of C. equisetifolia will be our next research focus.…”
Section: Discussionmentioning
confidence: 99%
“…Their contribution to the improvement of the growth of several plant species under saline conditions is well known [107,108] (Table 4). This is mainly related to a combination of biochemical, physiological, and nutritional effects [97,[109][110][111][112][113][114][115][116]. Among the mechanisms involved in salinity tolerance in AMF inoculated plants, we have the enhancement of water absorption capacity and nutrient uptake, the accumulation of osmoregulators like proline and sugars [105], the ionic homeostasis [87,117], and the reduction in Na + and Cl − uptake [118].…”
Section: Less Oxidative Damage Promoted Plant Growth and Enhancedmentioning
confidence: 99%